Interdependence Among the Brazilian States: An Input-Output Approach - Fernando Perobelli; Eduardo Haddad; Edson Domingues (European Regional Science Association (ERSA), 2006)
The principal aim of this paper is to evaluate the interregional linkages based on the many-region input-output table for Brazilian regions, for the year 1996, elaborated by FIPE. This work utilizes the extraction method by Strassert, 1968 and Schultz, 1977 and modified by Dietzenbacher et al (1993). Instead of extracting one sector from a sector-based model, we will examine the effects of hypothetically extracting a region from a many-region model. The method calculates the "backward linkages"; the "forward linkages" are obtained analogously from the matrix of allocation coefficients. The application of the methodology to the Brazilian inter-regional input-output tables shows that the states with high share in the Brazilian GDP presents a high degree of intra-regional interdependence both in terms of backward and forward linkages.
Keywords: 330